Evaluation of the photooxidation efficiency of As(III) applying the UVC/oxalate technique. (September 2017) - Jiang, Bo; Xin, Shuaishuai; He, Haihong; Liu, Xuyang; Gao, Li; Tang, Yizheng; Bi, Xuejun
Abstract: In this study, the photooxidation capacity of UVC/Oxalate (Ox) was evaluated using As(III) as a typical pollutant. The results show that the direct oxidation amount of As(III) induced by UVC in water was negligible, but the presence of Ox remarkably accelerated the oxidation rate of As(III). Under UVC irradiation, 50 μM As(III) can be completely oxidized to As(V) in the case of Ox concentration above 300 μM within 60 min. As(III) oxidation was found greatly related with the photodecomposition of Ox. Much more Ox can be mineralized in more acidic solution. At the same time, the photooxidation of As(III) was significantly favored at decreased initial pH from 8.0 to 3.0. In this reaction system, the role of oxygen was indispensable for Ox photodecomposition and As(III) photooxidation, which can be ascribed to its special roles as a precursor of reactive superoxide and an electron acceptor. In oxygen-present atmosphere, the in situ production of H2 O2 was detected during the photolysis of Ox and its photolysis product, i.e., OH primarily contributed to the oxidation of As(III). However, the photodecomposition of Ox and photooxidation of As(III) were significantly inhibited in the anaerobic environment. In general, the homogeneous photolysis of Ox in many commonly practiced UVC oxidation processes can be also proposed as a supplementary method of generating highly oxiditive species in aerobic condition. Highlights: The presence of oxalate can enhance the oxidation capacity of UVC irradiation. H2 O2 was produced in oxalate photolysis process under aeration condition. OH from H2 O2 played an primary role in enhancing As(III) oxidation. The production of photo-oxidants was dependent on solution pH and gas atmosphere.